Destination image of Bulgaria: Comparative analysis of representations of Bulgaria in state authorities' and UK and Irish tour operators' brochures and websites - Stanoeva, Diyana (2008)
Desttination image is becoming a popular topic, nowadays, when the tourism industry marks its boom. The importance of marketing destinations is believed to be an esential part of promoting destinations. The growing number of destinations, competing in the international marketplace, poses a challenging situation of a merciless competition among them. A destination's tourism authorities try to present their country at the best possible way as a perfect blend of culture, nature, unforgettable experiences, which will be able to attract tourists, thus increasing tourists' receipts in the destination. Bulgaria is an emerging destination on the worldwide tourism marketplace. A former Communist country and one of the new members of the European Union, the country is trying to find its place amongst the other competing destinations by offering tourists breathtaking scenery, rich cultural and historical heritage, hospitable people and delicious cuisine. Great Britain and Ireland are of a significant importance to Bulgaria, especially the UK is one of the primary markets for the country in terms of number of tourists. Six brochures produced by the Bulgarian State Agency of Tourism for marketing campaign 2008 and the official website of Bulgaria(www.bulgariatravel.org) will be analysed both in terms of content and images. Eleven British and Irish tour operators have been selected as a sample for evaluating their promotional tools(brochures and websites) about Bulgaria. A content analysis as a qualitative method is used to compare the two parties' promotional techniques. The results of the findings part of the disertation aim to find out what image of Bulgaria has been created by two independent but very important to tourists sources - the Bulgarian tourism authorities and tour operators from two major, for the country, target markets. The results from the comparison of the brochures and websites reveal that the image of Bulgaria created by the tour operators is cheap destination, whereas the BSTA presents the country as a destination of endless natural beauty, rich cultural and historical heritage, hospitable people and delicious food. The task of creating a strong brand image of a destination is extremely difficult, time consuming and challenging; however Bulgaria possesses a great potential to turn into a popular destination by taking advantage of all its tangible and intangible resources and by implementing effective marketing techniques.